How to make your housework more spiritual - Seise, Claudia (Azizah) (aboutislam.net, 2018)
Many of us have become accustomed to some form of help in our homes. For some of us, it is the cleaning lady that comes once a week. For others, they have cleaning, cooking, and driving personnel. Others have gardeners, security personnel, and baby sitters.